THE EFFECTS OF PHONOLOGICAL A WARENESS PROGRAM TO REDUCE ENGLISH READING DISABILITIES FOR INTERMEDIATE STAGE STUDENTS - Ismail, Nasrah Mahmoud (جامعة المنوفية - كلية التربية, 2010)
This study aimed at discovering the effectiveness of a proposed program for developing phonological awareness skills for dyslexic students. The final sample of this study is (77) females (M=13.4 years, SD = 0.577 years), it is divided into two groups; the experimental group consists of (40) girls and the control group consists of (37) girls. They were selected from Taif, Saudi Arabia. Students' phonological awareness skills and their reading skills were measured by a phonological awareness test and a diagnostic reading test that were designed by the researcher. The research applied continued for three months which included the proposed program. The data showed that there are statistically significant differences between the experimental group and the control group on the post-test diagnostic reading test as well as the phonological awareness tasks, showing a significant increase in reading skills in the experimental group. It also reveals that there are statistically significant differences between the pre-test and post-test results for the experimental group on the phonological awareness test and diagnostic reading test. This shows that the experimental group had an increase in skills after having participated in the program as seen on the post-test. In light of these results, the study provides a number of procedural recommendations that may contribute to raising the degree of the importance of phonological awareness training for the students with reading difficulties.
Keywords: التعليم المتوسط -- الأصوات -- تعلم القراءة -- تدريس اللغة الإنجليزية